Incretin mimetics as pharmacologic tools to elucidate and as a new drug strategy to treat traumatic brain injury. (1st February 2014) - Greig, Nigel H.; Tweedie, David; Rachmany, Lital; Li, Yazhou; Rubovitch, Vardit; Schreiber, Shaul; Chiang, Yung-Hsiao; Hoffer, Barry J.; Miller, Jonathan; Lahiri, Debomoy K.; Sambamurti, Kumar; Becker, Robert E.; et al.
Abstract : Traumatic brain injury (TBI), either as an isolated injury or in conjunction with other injuries, is an increasingly common event. An estimated 1.7 million injuries occur within the USA each year and 10 million people are affected annually worldwide. Indeed, nearly one third (30.5%) of all injury‐related deaths in the USA are associated with TBI, which will soon outpace many common diseases as the major cause of death and disability. Associated with a high morbidity and mortality and no specific therapeutic treatment, TBI has become a pressing public health and medical problem. The highest incidence of TBI occurs in young adults (15–24 years age) and in the elderly (≥75 years of age). Older individuals are particularly vulnerable to these types of injury, often associated with falls, and have shown increased mortality and worse functional outcome after lower initial injury severity. In addition, a new and growing form of TBI, blast injury, associated with the detonation of improvised explosive devices in the war theaters of Iraq and Afghanistan, are inflicting a wave of unique casualties of immediate impact to both military personnel and civilians, for which long‐term consequences remain unknown and may potentially be catastrophic. The neuropathology underpinning head injury is becoming increasingly better understood. Depending on severity, TBI induces immediate neuropathologic effects that, for the mildest form, may be transient; however, with increasing severity, these injuries cause cumulative neural damage and degeneration. Even with mild TBI, which represents the majority of cases, a broad spectrum of neurologic deficits, including cognitive impairments, can manifest that may significantly influence quality of life. Further, TBI can act as a conduit to longer term neurodegenerative disorders. Prior studies of glucagon‐like peptide‐1 (GLP‐1) and long‐acting GLP‐1 receptor agonists have demonstrated neurotrophic/neuroprotective activities across a broad spectrum of cellular and animal models of chronic neurodegenerative (Alzheimer's and Parkinson's diseases) and acute cerebrovascular (stroke) disorders. In view of the mechanisms underpinning these disorders as well as TBI, we review the literature and recent studies assessing GLP‐1 receptor agonists as a potential treatment strategy for mild to moderate TBI.